Synergistic effect of carotenoid and silicone-based additives for photooxidatively stable organic solar cells with enhanced elasticity. Issue 35 (14th July 2021) - Prete, Michela; Ogliani, Elisa; Bregnhøj, Mikkel; Lissau, Jonas Sandby; Dastidar, Subham; Rubahn, Horst-Günter; Engmann, Sebastian; Skov, Anne Ladegaard; Brook, Michael A.; Ogilby, Peter R.; Printz, Adam; Turkovic, Vida; et al.
Abstract : Bifunctional additive design for OPV provides joint improvement in (1) device lifetime via carotenoid and (2) flexibility via silicone. Abstract : Photochemical and mechanical stability are critical in the production and application of organic solar cells. While these factors can individually be improved using different additives, there is no example of studies on the combined effects of such additive-assisted stabilization. In this study, the properties of PTB7:[70]PCBM organic solar cells are studied upon implementation of two additives: the carotenoid astaxanthin (AX) for photochemical stability and the silicone polydimethylsiloxane (PDMS) for improved mechanical properties. A newly designed additive, AXcPDMS, based on astaxanthin covalently bonded to PDMS was also examined. Lifetime tests, produced in ISOS-L-2 conditions, reveal an improvement in the accumulated power generation (APG) of 10% with pure AX, of 90% when AX is paired with PDMS, and of 140% when AXcPDMS is added in the active layer blend, as compared to the control devices. Singlet oxygen phosphorescence measurements are utilized to study the ability of AX and AXcPDMS to quench singlet oxygen and its precursors in the films. The data are consistent with the strong stabilization effect of the carotenoids. While AX and AXcPDMS are both efficient photochemical stabilizers, the improvement in device stability observed in the presence of AXcPDMS is likely due to a more favorable localization of the stabilizer within the blend. The mechanical properties of the active layers were investigated by tensile testing and cohesive fracture measurements, showing a joint improvement of the photooxidative stability and the mechanical properties, thus yielding organic solar cell devices that are promising for flexible photovoltaic applications.